2016
DOI: 10.1038/cddis.2016.346
|View full text |Cite
|
Sign up to set email alerts
|

Increased expression of EHF via gene amplification contributes to the activation of HER family signaling and associates with poor survival in gastric cancer

Abstract: The biological function of E26 transformation-specific (ETS) transcription factor EHF/ESE-3 in human cancers remains largely unknown, particularly gastric cancer. The aim of this study was to explore the role of EHF in tumorigenesis and its potential as a therapeutic target in gastric cancer. By using quantitative RT-PCR (qRT-PCR), immunohistochemistry (IHC) and fluorescence in situ hybridization (FISH) assays, we investigated the expression and copy number of EHF in a cohort of gastric cancers and control sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
39
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 48 publications
(41 citation statements)
references
References 47 publications
2
39
0
Order By: Relevance
“…In breast cancer ProteoMix discovers three novel differentially methylated genes of diverse biological functions. ProteoMix detects a functional effect of hypo-methylation in the untranslated region (UTR) of EHF, which is a well-studied transcription factor involved in HER2 mediated epithelial differentiation (35); a likely oncogene, knockdown of EHF has been shown to inhibit tumor invasion and proliferation (36). Next, ProteoMix identifies hyper-methylation of FSTL1, an autoantigen that promotes immune response.…”
Section: Resultsmentioning
confidence: 99%
“…In breast cancer ProteoMix discovers three novel differentially methylated genes of diverse biological functions. ProteoMix detects a functional effect of hypo-methylation in the untranslated region (UTR) of EHF, which is a well-studied transcription factor involved in HER2 mediated epithelial differentiation (35); a likely oncogene, knockdown of EHF has been shown to inhibit tumor invasion and proliferation (36). Next, ProteoMix identifies hyper-methylation of FSTL1, an autoantigen that promotes immune response.…”
Section: Resultsmentioning
confidence: 99%
“…EHF was recently described to regulate HER3 levels in thyroid 57 and gastric cancer 58 and highlights its role in tumor progression. We showed that MET activation limits the cetuximab-induced HER2/HER3 mRNA levels.…”
Section: Discussionmentioning
confidence: 99%
“…We further identified that EHF is the TF that regulates HER2/HER3 expression following cetuximab administration. EHF was recently described to regulate HER3 levels in thyroid 57 and gastric cancer 58 and highlights its role in tumor progression. 67 However, here we also show that EHF plays a key role in the resistance to cetuximab by mediating the HER2/HER3 compensatory feedback loop.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…IHC assay was carried out to evaluate the levels of Ki67 in the xenograft tumors. The detailed protocol was described previously [21].…”
Section: Immunohistochemistry (Ihc)mentioning
confidence: 99%